Exploiting the role of long non-coding RNAs in the direct conversion of fibroblasts into functional cardiomyocytes - Correia, Paula Magda Teixeira (2020)
Heart disease is one of the leading causes of mortality in developed countries. The associated pathology is typically characterized by the loss of cardiomyocytes that leads, eventually, to heart failure. Presently, there are many promising strategies for cardiac regeneration. Direct cardiac reprogramming is becoming known as a novel therapeutic approach to regenerate injured hearts. Direct cardiac reprogramming is a simple and quick process however, the molecular mechanisms of cardiac reprogramming and cardiomyocyte-like cells functional maturation remain to be understood. Direct cardiac reprogramming has great potential to become one of the main strategies for regenerative medicine in heart failure since fibroblasts, contrary to cardiomyocytes which do not divide, are easily available in the heart, they are a large population of cells in the heart, which become activated and turn to myofibroblasts, contributing to fibrosis after cardiac injury. Currently it is known that a specific combination of three transcription factors, Mef2c, Gata4 and Tbx5 (MGT), are enough to reprogram non-myocyte mouse heart cells into induced cardiomyocyte-like cells. Nevertheless, human fibroblasts when infected with MGT appeared to have a small percentage of conversion. With MGT retrovirus we successfully transfected: mouse adult fibroblasts (MAFs), Feeders and Gm 03348 (human fibroblasts with 10 years old). Through qPCR analysis we evaluated the expression of lncRNAs: Gm 15856, Mir22hg, Gm 027028 and Gm 28592. Our goal was to understand which lncRNAs are the best candidates to knockdown in order no enhance direct cardiac reprogramming. In addition, we studied how nutrient manipulation in cell culture media can influence direct cardiac reprogramming. It was found that media with higher levels of glucose and glutamine had larger rates of cellular survival and proliferation.